Pelatihan Penulisan Artikel Ilmiah pada Jurnal Nasional bagi Guru SMA Sederajat di Kabupaten Rokan Hilir Provinsi Riau - Isjoni Isjoni; Bunari Bunari; Yuliantoro Yuliantoro (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2021)
This service activity aims to improve understanding and practice writing skills and submit scientific articles to national journals for high school teachers and equivalent in Tanah Putih sub-district, Rokan Hilir Regency. This activity was carried out using workshop method and continued with online guidance. In the field workshop, material was presented on the definition of scientific articles and journals, why teachers are required to have the ability to research and write articles, write scientific articles and training in submitting scientific articles to online journals. The results of the training showed an increase in the ability of participants to understand the procedures for writing scientific articles and the procedure for submitting articles to national journals. The core achievement can be seen from the enthusiasm of the participants who were very good during the training and there were articles from participants who had succeeded in being submitted to reputable National Journals.